Characterization And Antifungal Activity Evaluation Of Tamanu Seed Oil Based Liquid Soap Towards Candida Albicans - Devi Puji Rahayu; Nur Khanifah; Rofikoh; Mochammad Chasani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Candida albicans fungal infection towards skin could be prevented by using the soap with antifungal activity. Material used for the soap making was tamanu oil which was potential as antifungal soap. This study aims to find out the best characteristic liquid soap and to evaluate its antifungal activity towards Candida albicans. The methods used in this research were maseration and followed by soap making using semi-boiled method. Tamanu seed oil based liquid soap was formulated with variety concentrations of bacang leave extract as an antifungal agent and nutmeg leave extract as foaming agent. Each soap were characterized following the SNI 4085:2017 standard. The liquid soap formula with the best characteristic was determined and its antifungal activity towards Candida albicans was tested using disk diffusion method. The result shows that the best soap formula is the tamanu oil based liquid soap with the addition of 0.9% bacang leave extract and 0,9% nutmeg leave extract (SFM5P5). The best formula had 9.25 pH value; 18,3017% total active agent, 3,3840% free fatty acid; 1,0235 g/mL density and 94,1176% foam stability. In conclusion, liquid soap has strong activity to inhibit the fungal growth of Candida albicans with 18.18 mm of inhibition zone diameter.